Chroicocephalus ridibundus Linnaeus 1766 ... - Bishop, K. David (Zenodo, 2023)
**BLACK-HEADED GULL Chroicocephalus ridibundus Status Vagrant. Scarce Palearctic migrant to New Guinea waters (Beehler & Pratt 2016) with just two records on Biak. 29‒30 March 1963: an immature in Biak harbour (King 1979); February 1991: eight at Biak wharf (Gibbs 1993). ... : Published as part of Bishop, K. David, 2023, The avifauna of Biak Island, Papua, Indonesia with comments on status, conservation, natural history and taxonomy, pp. 3-62 in Bulletin of the British Ornithologists' Club 143 (1) on page 34, DOI: 10.25226/bboc.v143i1.2023.a2, http://zenodo.org/record/11642130 ...